Time and cost optimization of business process RMA using PERT and goal programming - Gita Intani Budiawati; Riyanarto Sarno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
As a company engaged in the distribution of wireless devices, Return Material Authorization (RMA) is a mandatory service that must be owned by the company. RMA is a part of the process of returning a product to receive a refund, replacement, or repair during the product’s warranty period. The business process of RMA used functionally design, which is not considered to be effective in terms of time and cost for the company of 2880 minutes for IDR 348242. In this research, Project Evaluation and Review Technique (PERT) was used to select the optimal traces; to optimize time and cost, the researcher used goal programming. This technique allows the creation of a controlled and orderly activity because the schedule and budget of a job are predetermined prior to the implementation. The optimization results show that the process time is reduced by 50% and the cost is reduced by almost 55% which show improvement on the performance of the business processes.